PANORAMIC DETECTION FOR DENTAL ANOMALIES OF PATIENTS WITH STROKE - Al-Tamemi, Zainab A.H. (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
In the panoramic radiographs that were taken of the people who had just been accepted into dental school, calcifications in the region of the carotid vasculature could be identified in 4.5 percent of the 300 patients. This information was gleaned from the examination of the patients' medical histories. The people who had calcifications were questioned by the authors to see whether or not those patients displayed any known risk factors related with atherosclerosis. Obesity and atherosclerosis were shown to have a link in the patients who were questioned, and one of the patients reported experiencing symptoms of atherosclerosis. This relationship was demonstrated to have a statistically significant connection in the patients who were questioned. The authors came to the conclusion that panoramic radiography is helpful in the identification of some asymptomatic individuals who have carotid calcifications. This was one of the conclusions that they reached. After conducting the necessary study, they came to this conclusion. These persons should make an appointment with their primary care physicians as soon as it is humanly possible so that they can have a cerebrovascular workup as part of a preventative approach to lower the likelihood of having a stroke.